Application of Probiotics in Shrimp Aquaculture: Importance, Mechanisms of Action, and Methods of Administration. Issue 4 (1st October 2016) - Kumar, Vikash; Roy, Suvra; Meena, Dharmendra Kumar; Sarkar, Uttam Kumar
ABSTRACT: Shrimp aquaculture is the fastest growing animal food producing sectors in the world due to its high demand in developed countries; however, they are affected by diseases mainly caused by opportunistic pathogens results in huge economic losses. Today preventive and management measures are central concern to overcome such outbreak of diseases. The adverse effect of chemotherapeutics in shrimp farming has drawn attention for the development of non-antibiotic and environment friendly agents, which is one of the key factors for health management in shrimp aquaculture. In recent years, application of probiotics against virus and bacteria in shrimp farming had been a novel and safe approach since they promote the innate immune response. Probiotics for bacterial diseases like vibriosis is well reported, but for viral diseases, the authentic strains still need research. Apart from the discovery of new or better formulations, improvement in the probiotic benefits may be helpful. Thus, better and economic production methods, administration ways or combination with other preventive/therapeutic measures are welcomed. Further studies are still necessary to increase the knowledge about use of probiotics to control bacterial infections in shrimp but much more efforts are needed in the case of viral diseases. In this review, potential application of probiotics in shrimp aquaculture: importance, mechanisms of action and methods of administration are being focused. The article also explains the limitations and prospects of probiotics in sustainable and ecofriendly shrimp culture to augment the total shrimp aquaculture production.